A new species of Elisama Giebel, 1856 (Blattaria: Blattulidae) discovered in mid-Cretaceous Kachin amber of northern Myanmar - Sendi, Hemen (Zootaxa, 2025)
Elisama Giebel, 1856 is a cockroach genus of the family Blattulidae Vishniakova, 1982 ranging from the Late Jurassic to the Late Cretaceous. Elisama kacerovae sp. nov. is herein described based on a completely preserved adult, and it is the first representative of the genus in Cenomanian northern Myanmar amber. It differs from other species of Elisama in being smaller in size, having a darkly striated pronotum with translucent nota and in the forewing with stem of M appressing R in the basal half of the wing. Elisama shares a dark macula on the forewings with Vrtula Vršanský, 2008, Huablattula Qiu, Wang et Che, 2019, Svabula Vršanský, 2005, Nogueroblatta Martínez-Delclòs, 1993 and Spono Vršanský, 2024. Some blattulid genera, such as the former four, are likely in need of revision. Except for E. globosa from Mdeyrij-Hammana amber in Lebanon, all species were discovered in sedimentary rocks of former Gondwana and Laurasia. It is possible that representatives of Elisama mainly prospered in less humid environments with milder climate instead of tropical forest ecosystems, where they were apparently rare in the fossil record, although taphonomic bias cannot be ruled out completely.